Variasi Ortografi Khusus Pegon Dalam Teks Syi'ir Tandha Qiyamat - Irakusuma, Ratna Nur Fatimah; H, Hendrokumoro (INC- Islam Nusantara Center, 2024)
This study aims to identify Pegon specific orthographic variations (Pegon special script). The special Pegon script referred to in this study is a script that represents Javanese sounds that are not possessed by Arabic sounds. The consonant sounds mentioned above are /c/, /g/, /p/, /ṭ/, /ḍ/, /ŋ/, and /ñ/. Each of the phonemes mentioned above has at least two variations of orthographic shapes. These variations are in the form of the position of the graphem in the word, the presence or absence of dots, and the number of dots in the script in question. The adoption and adaptation of Hijaiah graphemes into Pegon's special graphemes tends to be based on the proximity of the original grapheme articulation point into the fabricated graphem or the similarity of the resulting sound. Grapheme modifications carried out in the adaptation process are in the form of modifying the number of points in the Hijaiah script that have dots and adding a single point to the Hijaiah script that does not have points. Combining philological methods with linguistic orthographic theory, this study gives a new color to the study of language descriptions, especially Javanese. Penelitian ini bertujuan untuk mengidentifikasi variasi ortografi khusus Pegon (aksara khusus Pegon). Aksara khusus Pegon yang dimaksud dalam penelitian ini adalah aksara yang mewakili bunyi bahasa Jawa yang tidak dimiliki oleh bunyi bahasa Arab. Bunyi-bunyi konsonan yang disebutkan di atas adalah /c/, /g/, /p/, /ṭ/, /ḍ/, /ŋ/, dan /ñ/. Masing-masing fonem yang disebutkan di atas memiliki sekurang-kurangnya dua variasi bentuk ortografi. Variasi tersebut berupa posisi grafem dalam kata, ada tidaknya titik, dan jumlah titik pada aksara yang bersangkutan. Adopsi dan adaptasi grafem Hijaiah ke dalam grafem khusus Pegon cenderung berdasarkan kedekatan titik artikulasi grafem asal ke dalam grafem rekaan atau kemiripan bunyi yang dihasilkan. Modifikasi grafem yang dilakukan alam proses adaptasi berupa modifikasi jumlah titik pada aksara Hijaiah yang memiliki titik dan penambahan titik tunggal pada aksara Hijaiah yang tidak memiliki titik. Memadukan metode filologi dengan teori ortografi linguistik, penelitian ini memberi warna baru dalam penelitian deskripsi bahasa khususnya bahasa Jawa.